A Survey of Receiver Designs for Cooperative Diversity in the Presence of Frequency Offset - Al-Khalid, Hj Othman; Hushairi, Zen; Ong, Sylvia Ai Ling; Mahmood, Adnan (IJCSIS, 2015)
Cooperative diversity is becoming a potential solution for future wireless communication networks due to its capability to form virtual antenna arrays for each node (i.e. user). In cooperative networks, the nodes are able to relay the information between the source and the desired destination. However, the performance of the networks (for instance – mobile networks, ad-hoc networks and vehicular networks) is generally affected by the mobility of the nodes. As the nodes’ mobility rapidly increases, the networks are subjected to frequency offset and unknown channel properties of the communication links which degrades the system’s performance. In a practical scenario, it is a challenging task and impractical for the relay and destination to estimate the frequency offset and channel coefficient especially in timevarying environment. In this manuscript, a comprehensive survey of existing literature for receiver designs based on Double Differential (DD) transmission and Multiple Symbol Detection (MSD) approach is presented to eliminate the complex channel and frequency offset estimation.